2011
DOI: 10.1021/ja107691w
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Conformational Change and Product Release in DNA Repair by (6−4) Photolyase

Abstract: Proteins of the cryptochrome/photolyase family share high sequence similarities, common folds and the flavin adenine dinucleotide (FAD) cofactor, but exhibit diverse physiological functions. Mammalian cryptochromes are essential regulatory components of the 24-hour circadian clock, whereas (6-4) photolyases recognize and repair UV-induced DNA damage by using light energy absorbed by FAD. Despite increasing knowledge about physiological functions from genetic analyses, the molecular mechanisms and conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
(114 reference statements)
0
27
0
Order By: Relevance
“…Thus, positioning a phosphate ion near the substrate and cofactor binding sites may provide both eukaryotic PHR families with control mechanisms for constraining and regulating their active sites. Phosphate-induced protein conformational changes could adjust intra-or intermolecular hydrogen bonds to aid electron transfer, DNA distortion, base flipping, or product release during the repair process (44).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, positioning a phosphate ion near the substrate and cofactor binding sites may provide both eukaryotic PHR families with control mechanisms for constraining and regulating their active sites. Phosphate-induced protein conformational changes could adjust intra-or intermolecular hydrogen bonds to aid electron transfer, DNA distortion, base flipping, or product release during the repair process (44).…”
Section: Resultsmentioning
confidence: 99%
“…where η 1 and η 2 are the quantum yields of the first and second photoreaction, respectively. Substrate binding and product release are expected15 to be much faster than the overall repair rate (less than 0.01 s −1 in all our experiments) and are hence considered to be non‐limiting (Supporting Information, Section 4).…”
Section: Methodsmentioning
confidence: 99%
“…The investigators observed a key cyclic proton transfer step between an active-site histidine residue and the substrate, which occurs in 425 ps and leads to 6 -4 PP repair in tens of nanoseconds . In addition, time-resolved experiments of Xenopus laevis (624) photolyase uncovered a drastic diffusion change, which was assigned to the rapid dissociation (time constant of 50 ms) of the protein from the repaired DNA product (Kondoh et al 2011). Later on, 6-4 PP repair mediated by the same enzyme was investigated using Fourier transform infrared (FTIR) spectroscopy .…”
Section: Advances In the Structural And Functional Relationship Of (6mentioning
confidence: 99%